Effects of long COVID on healthcare utilization - Michael Gottlieb; Erica S. Spatz; Huihui Yu; Imtiaz Ebna Mannan; Michelle Santangelo; Caitlin Malicki; Nicole L. Gentile; Rachel E. Geyer; Alex Charlton; Jonathan W. Dyal; Joann G. Elmore; Kristyn Gatling; et al. (PLoS ONE, 2025)
Background While most research on Long COVID (LC) has focused on symptoms and quality of life, there remains a critical need to better understand the effect of LC on resource utilization. This study sought to determine the type and amount of healthcare utilization among participants with versus without LC. Methods This was a secondary analysis of a prospective, longitudinal, multicenter U.S. study of adult participants with symptomatic COVID-19, confirmed with testing, who completed 3-month post-infection surveys and had electronic health record data for at least 180 days pre- and post-index testing. We excluded participants with any COVID-19 infections within the 6 months following enrollment. Consistent with prior work, LC was defined as ≥3 post-infectious symptoms at 3 months, while those with <3 symptoms were categorized as not having LC. Our primary outcome was to compare the change in visit types between pre- and post-index testing (hospitalization, emergency department visit, office visit, procedure, telehealth, and other). As secondary outcomes, we assessed differences in visit complexity using the summative length of each encounter for each category as a measure of total healthcare usage. Results A total of 847 participants met inclusion criteria (179 LC, 668 non-LC). When compared with the pre-index period, there was an overall increase in visit numbers of all six visit categories during the post-index period for all groups, most pronounced in office and telehealth visits. When compared with the non-LC group, the LC group was less likely to have ED visits (OR: 0.1; 95% CI 0.0–0.5). However, among those with LC who had at least one hospitalization, they were more likely to have additional hospitalizations (OR: 2.6; 95% CI 1.5–4.6). Visit length for office visits and hospitalization in the LC group was increased when compared with the non-LC group, though this diminished after adjustment for patient baseline characteristics. Conclusions All participants who were infected with SARS-CoV-2 had a marked increase in healthcare utilization during the subsequent 180 days. The LC group had significantly higher rates of additional hospitalization compared with those without LC, which may help to inform healthcare resource planning.